Islam dan Rasialisme di Kashmir dalam Kacamata Sejarah - Satrio Alif Febriyanto (UIN Sumatera Utara Medan, 2021)
As a border area between India and Pakistan, Kashmir has been a conflict area since those countries became independent from British rule in 1947. With the fact that it is the only province in India with a Muslim majority population, Kashmir has become an anomaly for India, which is the country with the largest Hindu population in the world. This condition certainly makes Muslims living in Kashmir vulnerable to being the target of repression by the Hindu community. The purpose of this study was to determine the causes of racism in Kashmir from a historical perspective. Meanwhile, The historical research method used in this research is juridical research with a secondary historical source written on the theme of Indian history and culture which aims to review and analyze the root causes of conflict between Muslims and Hindu communities based on a historical perspective. Based on the results of research that has been done, the reasons of the conflict between Muslims and the Hindu community in Kashmir is the difference teachings of the two religions and the historical background of the relationship between the two religions since the first time Islam entered India.